From Somnath to Babri: Blame it on religion? - Banerjee, Paritosh (Kolkata: [s.n.], 2005)
Sums up Communal violence or riots in the post Independence India for public awareness of the issues involved. About communal violence.
Towards a definition -- The Muslim questions are the Muslim foreigners -- The birth of Hindu nations- more an instrument for capture of power than a philosophy -- A demography-not faith but a sence of deprivation and alienation -- Globalisation -- riots -- Toward reconciliation -- Conclusion -- A postscript.
Keywords: Religion and Politics; Political Science